2011
DOI: 10.4310/atmp.2011.v15.n5.a2
|View full text |Cite
|
Sign up to set email alerts
|

Model building with $F$-theory

Abstract: Despite much recent progress in model building with D-branes, it has been problematic to find a completely convincing explanation of gauge coupling unification. We extend the class of models by considering F -theory compactifications, which may incorporate unification more naturally. We explain how to derive the charged chiral spectrum and Yukawa couplings in N = 1 compactifications of F -theory with G-flux. In a class of models which admit perturbative heterotic duals, we show that the F -theory and heterotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
1,202
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(1,228 citation statements)
references
References 83 publications
10
1,202
0
10
Order By: Relevance
“…This way, F-theory can be considered as a 12-dimensional string theory compactified on a torus characterised by the above modulus τ . Algebraically, the fibration is described by a birationally equivalent complex cubic equation, the so called Weierstraß model [2][3][4]. Depending on the specific structure of its coefficients, at certain points of the fibration the torus degenerates and the fibration becomes singular.…”
Section: Jhep10(2015)041mentioning
confidence: 99%
See 3 more Smart Citations
“…This way, F-theory can be considered as a 12-dimensional string theory compactified on a torus characterised by the above modulus τ . Algebraically, the fibration is described by a birationally equivalent complex cubic equation, the so called Weierstraß model [2][3][4]. Depending on the specific structure of its coefficients, at certain points of the fibration the torus degenerates and the fibration becomes singular.…”
Section: Jhep10(2015)041mentioning
confidence: 99%
“…In this context, one may determine the massless spectrum of the effective theory and all its properties under the GUT group and its quantum numbers with respect to the symmetries of the spectral cover. Furthermore from general characteristics of the compact manifold and G-fluxes [3] we can determine the chiralities of the massless spectrum.…”
Section: Jhep10(2015)041mentioning
confidence: 99%
See 2 more Smart Citations
“…Ignoring the details of how this happens for the concrete geometry under consideration it has been shown that by degenerating the fourfold in a controlled way viable phenomenological low energy particle spectra will emerge in four dimensions as was worked out in the F-theory revival starting with the papers of [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%